SLANG DALAM SITUS 9GAG.COM: SUATU KAJIAN SOSIOLINGUISTIK - , LATIF AMRULLAH; , Prof. Dr. I Dewa Putu Wijana., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research entitles Slang in 9gag.com site: The Sociolinguistics Study. In its processes, this research is based on the four aims to be achieved. First, to describe the forms and the formation process of slang used in 9gag.com. Second, to describe the relatedness of meaning and the alteration of meaning of slang from its original form. Third, to describe the functions of slang usage in 9gag site. Fourth, to describe the social factors influencing the existence of slang in 9gag.com site. The form of this research is qualitative descriptive which results descriptive data. The data are collected by using observations method on the comments which follow certain postings of pictures or videos. Then the method is followed by full observation method, hence there is no interference from the researcher on the data collected. The next steps, the data analysis is conducted based on the Hymesâ sociolinguistics approach (1974) which relates slang and social factors, and also slang as a language variation proposed by Partridge (1954) about the functions of employing slang. Based on the observations and data analysis, the results of this research are as follows. The first, the form of slang can be classified as words, phrases and sentences. Besides, there are some patterns of word formation which go off from the English standard grammatical rules. The second, the alteration of meaning is the result from the needs of users about certain vocabularies which seems more appropriate to use. Furthermore, euphemism is very important because the users try to deliver swear words by using more polite words. The third, there are two additional functions of slang to add up what Partridge (1954) had proposed: slang as mocking and slang as appraisal. The fourth, the social factors proposed by Hymes (1974) are very influencing on the appearance and the existence of slang. The fifth, the users of this site create their own language community which is widely open and is not limited from geographical factor. The sixth, the use of slang in the internet becomes the form of language freedom for its users because they can use their own language without anyone knows who they are.